"Ptychoparioid" trilobites of the Harkless Formation and Mule Spring Limestone (Cambrian Series 2, Stage 4), Clayton Ridge, Nevada. (July 2022) - Sundberg, Frederick A.; Webster, Mark
Abstract: Early "ptychoparioid" trilobites are likely to play a crucial role in determining the currently unresolved phylogenetic relationships among the numerous Cambrian libristomate clades. However, such phylogenetic analyses are hindered by the fact that many species and genera of early "ptychoparioids" are known from very limited material and are typically defined only on cranidial features. Herein, we report new "ptychoparioid" assemblages from the Saline Valley Tongue, Harkless Formation at Clayton Ridge, Nevada. These middle to upper Dyeran Stage (Cambrian Series 2, Stage 4) assemblages contain well-preserved early "ptychoparioids" that are represented by articulated exoskeletons as well as isolated cranidia, rostral plates, librigenae, thoracic segments, and pygidia, which together provide morphological details for the complete or nearly complete exoskeleton of three new genera and four new species: Anebocephalus silverpeakensis n. gen. n. sp.; Coenoides scholteni n. gen. n. sp.; Harklessaspis rasettii n. gen. n. sp.; and H . parvigranulosus n. gen. n. sp. Pending a formal phylogenetic analysis, it is deemed preferable to assign these taxa to new genera rather than to shoehorn them in to potentially ill-diagnosed existing genera. These new genera are compared to the Cambrian Series 2 taxa Crassifimbra and Eokochaspis, and the Miaolingian Series taxon Elrathina, which are similar in morphology and known from sclerites other than just cranidia. Also documented in this study are the "ptychoparioids" Crassifimbra walcotti, Cr .? sp. A, Cr . sp. B, and "ptychoparioid" spp. A, B, C, and D from the Saline Valley Tongue and the overlying Mule Spring Limestone and lowermost Emigrant Formation. UUID: http://zoobank.org/864d4005-2676-4f3f-b676-911efde7d263